An RNA-based system to study hepatitis B virus replication and evaluate antivirals - Yu, Yingpu; Schneider, William M.; Kass, Maximilian A.; Michailidis, Eleftherios; Acevedo, Ashley; Pamplona Mosimann, Ana L.; Bordignon, Juliano; Koenig, Alexander; Livingston, Christine M.; van Gijzel, Hardeep; Ni, Yi; Ambrose, Pradeep M.; et al. (Science advances, 2023)
Hepatitis B virus (HBV) chronically infects an estimated 300 million people, and standard treatments are rarely curative. Infection increases the risk of liver cirrhosis and hepatocellular carcinoma, and consequently, nearly 1 million people die each year from chronic hepatitis B. Tools and approaches that bring insights into HBV biology and facilitate the discovery and evaluation of antiviral drugs are in demand. Here, we describe a method to initiate the replication of HBV, a DNA virus, using synthetic RNA. This approach eliminates contaminating background signals from input virus or plasmid DNA that plagues existing systems and can be used to study multiple stages of HBV replication. We further demonstrate that this method can be uniquely applied to identify sequence variants that confer resistance to antiviral drugs.
Gesehen am 09.08.2023